COVID-19 pandemic: Lessons for spatial development - Mazda Adli; Sabine Baumgart; Klaus J. Beckmann; János Brenner; Gabriele Bolte; Stefan Gärtner; Andrea Hartz; Carola Havekost; Dietrich Henckel; Heike Köckler; Caroline Kramer; Sebastian Krätzig; et al. (Verlag der ARL - Akademie für Raumentwicklung in der Leibniz-Gemeinschaft, 2022)
[Background and aims of this position paper] Since the COVID-19 pandemic began, it has become ever clearer that it poses an enormous challenge for society. The lockdown imposed on large parts of public life, which hit all social groups and institutions relatively abruptly with a wide range of impacts, as well as the measures adopted subsequently have resulted in radical changes in our living conditions. In some cases, the crisis has acted as an accelerator of trends affecting processes that were already ongoing: the digitalisation of communications and educational processes, the growth in working from home and mobile working arrangements, the expansion of online retail, changes in travel behaviour (in favour of cars and bicycles), and the establishment of regional service networks. At the same time, there has been a braking effect on sectors such as long-distance travel, global trade, trade fairs and cultural events, as well as on progress towards gender equality in the division of labour for household responsibilities and childcare. Socio-spatial, infrastructural, economic and ecological effects are becoming increasingly apparent. For those involved in spatial development and spatial planning, urgent questions arise not only about the weaknesses that have become apparent in our spatial uses in terms of infrastructure and public service provision, the economy and ecology, and in our ways of life in terms of housing and the supply of goods and services, but also about what opportunities have emerged for sustainable and self-determined lifestyles. What conclusions for anticipatory and preventive planning can be drawn from these (provisional) findings? Using a critical, multidisciplinary and integrative examination of the spatially-relevant effects of the COVID-19 pandemic, this paper establishes connections between the crisis management of today and crisis preparedness concepts for potential future pandemics. Building on that, it proposes corresponding recommended actions. These actions relate not only to insights for medium-term space-related crisis management but also to conclusions on long-term strategic challenges for spatial development in view of pandemics to be expected in the future. For this position paper, the 'Pandemic and Spatial Development' Ad hoc Working Group at the ARL - Academy for Territorial Development in the Leibniz Association has compiled interdisciplinary perspectives from spatial development and spatial planning, public health services, epidemiology, economics and social sciences, and has condensed them into transdisciplinary recommendations for action. These recommendations are directed at the various action levels for spatial development and spatial planning.
urn:nbn:de:0156-01370
Keywords: 710; Coronavirus; Raumordnung; Regionalplanung; Raumstruktur; Gesundheitsversorgung; Versorgungswirtschaft; Deutschland; EU-Staaten